A proposed mechanism for the MDMA-mediated extinction of traumatic memories in PTSD patients treated with MDMA-assisted therapy - Sottile, Robert J.; Vida, Thomas (Frontiers in Psychiatry, 2022)
Post-traumatic stress disorder (PTSD) is a devastating psychiatric disorder afflicting millions of people around the world. Severe anxiety, intrusive thoughts, pervasive nightmares, an assortment of somatic symptoms, associations with severe long-term health problems, and an elevated risk of suicide characterized PTSD. As much as 40-70% of patients suffer from refractory disease. MDMA (3,4-methylenedioxy-methamphetamine) and other psychedelics have been used to enhance the efficacy of psychotherapy almost since their discovery. However, due to it’s FDA schedule 1 classification with perceived potential for abuse and no accepted medical use, research has been limited into the mechanism by which MDMA produces improvement in PTSD symptomology. Nevertheless, several compelling rationales have been explored, with the pro-social effects of MDMA thought to enhance therapeutic alliance and thus facilitate therapist-assisted trauma processing. This explanation, while likely true in part, is inadequate. Thus, molecular explanations such as MDMA mediated increased BDNF availability in the fear memory learning pathways are necessary to account for the profound efficacy of MDMA-assisted psychotherapy.